Interest Rate Hysteresis in Macroeconomic Investment under Uncertainty - Ansgar Belke; Matthias Göcke (Global Labor Organization (GLO), 2019)
The interest rate is generally considered as an important driver of macroeconomic investment. As an innovation, this paper derives the exact shape of the “hysteretic” impact of changes in the interest rate on macroeconomic investment under the scenarios of both certainty and uncertainty. We capture the direct interest rate-hysteresis on the investments and the capital stock and, explicitly, of stochastic changes on the interest rate-investment hysteresis. Starting with hysteresis effects on a microeconomic level of a single firm, we apply an explicit aggregation procedure to derive the interest rate hysteresis effects on a macroeconomic level. Based on our simple model we are able to obtain some conclusions about the efficacy of a central bank's interest rate policy, e.g. in times of low or even zero interest rates and high uncertainty, in terms of stimulating macroeconomic investment.
Keywords: C61; E22; E44; 330; Forward guidance; interest rate; investment; Mayergoyz-Preisach model; monetary policy; path dependence; non-ideal relay; sunk-cost hysteresis; uncertainty; zero lower bound